Framework for multi-purpose utility tunnel lifecycle cost assessment and cost-sharing. (October 2020) - Alaghbandrad, Ali; Hammad, Amin
Highlights: Proposing a method for MUT lifecycle cost assessment. Proposing a method for MUT lifecycle cost-sharing. Improving fairness in MUT lifecycle cost-sharing. Considering risk and benefit factors in the proposed MUT cost-sharing method. Abstract: The traditional method of buried utilities (i.e. water, sewer and gas pipes, and electrical and tele-communication cables) has been using for many decades particularly in urban areas. Repeated excavations are needed to access these underground utilities for maintenance, repair, and renewal activities. Urban areas have been experiencing many street closures and traffic disruptions because of excavation for maintaining underground utilities. These construction works have imposed major costs on public and private utility providers as well as on citizens and local businesses (social cost). Multi-purpose Utility Tunnel (MUT) was introduced as a solution that not only avoids these excavations, but also facilitates inspection and protects utilities. However, MUT is not widely used in most of the countries, because of the high initial investment, safety and security issues, complicated design and construction, and complex coordination of utility companies. Despite the higher design and construction cost of MUT, operational cost-savings can justify the investment from the project point of view. From the organization's point of view and based on cost-sharing, MUT should be more economical as well and the MUT benefits should be distributed fairly, to convince utility companies to participate in the MUT project. Lifecycle Cost (LCC) analysis of MUT and buried utilities method is complicated because of various factors that influence LCC. This paper aims to develop a comprehensive and systematic model for MUT and buried utilities LCC analysis by considering the influencing factors. The output of this model determines the LCC of MUT and buried utilities to ensure the project decision-makers that MUT is the economic method. This model also proposes a model of MUT cost-sharing to ensure the decision-makers of utility companies that MUT is the economic method for their company and also all the utility companies benefit from MUT fairly. This model defined the fairness based on three principals: (a) balance of risk, (b) balanced benefit-cost ratio, and (c) balance in contributed benefit and gained benefit. It is expected that the proposed model promotes using MUT by facilitating economical analysis and decision making for MUT projects from project and organization points of view.